Analisis Faktor yang Mempengaruhi PUS Mengikuti Keluarga Berencana (KB) di Wilayah Kerja Puskesmas Sambirejo Kabupaten Sragen - Prasetyo, Tri, Sulastri, S.Kp., M.Kes, Endang Zulaicha, S.Kp (2013)
The new family planning program within this paradigm are very pressing mission importance of respect for reproductive rights as integral to improving the quality of family. More use of contraceptives in urban areas with relatively high socioeconomic level. A wide range of contraceptive use in low levels. Another factor was the acceptor worried about the side effects of contraceptives such as the increase in weight. The purpose of this study was to analyze the factors that affect the follow family planning health centers in the region of Sragen Sambirejo. This research was a descriptive study with cross sectional correlative. The study population was at the Sub Sukorejo Sambirejo Sragen. The research sample esbanyak 84 with proportional random sampling technique. Research instrument in the form of a questionnaire. The analysis technique was the Chi Square test. The results of this study indicate: (1) There was no effect of age on participation planning, (2) there was no effect of education on participation planning, (3) there was no income effect on participation planning, and (4) are influences knowledge KB EFA the participation of family planning in Sub Sukorejo Sambirejo Sragen district in October 2012. The better knowledge about family planning which means they are more understanding of the benefits and disadvantages of family planning have an impact on the onset of conviction to follow the family planning program and participation embodied in planning family.